Documentos sobre oficinas de correo "Postmaster" de Comerío - Todd, Roberto H.; Bartlett, John H. (My University, 1922)
Documentos sobre oficinas de correo.
Keywords: Postal service--Puerto Rico.; Servicio postal--Puerto Rico.; Valldejuly, Rafael J.; Pacheco, Gloria B.; Guzmor, Feliciana G.